2005
DOI: 10.1002/pts.674
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of cold‐stored guavas influenced by package materials

Abstract: The objective of this study was to evaluate the influence of package materials on the preservation of cold-stored 'Kumagai' guavas. The treatments were: PO2, coextruded polyolephinic film with gas injection (5% O 2 /5% CO 2 /N 2 ); PO3, coextruded polyolephinic film with gas injection (5% O 2 /5% CO 2 /N 2 ); LDPE, linear low density polyethylene film; LDPE-gas, linear low density polyethylene film with gas injection (3% O 2 /8% CO 2 /N 2 ); PVC, polyvinylchloride stretch film; PO1, co-extruded polyolephinic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
2
5
0
4
Order By: Relevance
“…Many researches worked on MAP on guava fruit using different packaging materials at different gas concentration and storage temperature. They reported that the quality of guava fruit retained in 25–50‐µm LDPE film at 5–10 °C storage temperature . However incorrect use of MAP or the use of an inappropriate MA film, gas concentration and storage temperature could result in anaerobic conditions leading to product spoilage…”
Section: Introductionmentioning
confidence: 99%
“…Many researches worked on MAP on guava fruit using different packaging materials at different gas concentration and storage temperature. They reported that the quality of guava fruit retained in 25–50‐µm LDPE film at 5–10 °C storage temperature . However incorrect use of MAP or the use of an inappropriate MA film, gas concentration and storage temperature could result in anaerobic conditions leading to product spoilage…”
Section: Introductionmentioning
confidence: 99%
“…However, MAP often results in development of undesirable fermentation because of insufficient permeability of the packaging film, which might cause formation of ethanol, acetaldehyde, and off-flavors and odors (Jacxsens et al, 2000;Day, 2001). Packaging films with improved permeability have been studied and developed successfully to improve MAP conditions (Garcia et al, 1998;Van der Steen, 2002;Jacomino et al, 2005), and silicone membrane system, which consists of a tergal net covered with a thin and uniform layer of siliconee rubber, was an effective packaging film for MAP (Vigneault et al, 1992). Gariepy et al (1986) used a silicone membrane system for long term storage of celery under controlled atmosphere conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Empaques pla´sticos Jacomino et al, 2005 21 dı´as a 10 8C y despue´s almacenadas a T ambiente. Guayabas empacadas con pelı´culas a base de:…”
Section: Bautista and Silva 1997unclassified
“…La guayaba es una fruta altamente perecedera, susceptible a dan˜os meca´nicos y por frı´o (Mercado et al, 1998;Jacomino et al, 2005). Algunos autores la clasifican como un fruto no climate´rico, pero la mayorı´a coincide con el comportamiento climate´rico (Akamine & Goo, 1979;Brown & Willis, 1983;Mercado et al, 1998).…”
unclassified
See 1 more Smart Citation